2018
DOI: 10.3171/2017.8.peds17379
|View full text |Cite
|
Sign up to set email alerts
|

Orbital lymphatic-venous malformation with concomitant spontaneous orbital arteriovenous fistula: case report

Abstract: The authors describe the case of an 11-year-old boy with no history of prior trauma, who experienced acute proptosis and visual loss while showering. Diagnostic carotid artery angiography revealed an orbital lymphatic-venous malformation (LVM) concomitant with an intraorbital arteriovenous fistula. The patient was treated with transvenous coil and N-butyl cyanoacrylate glue embolization, combined with direct percutaneous glue injection into the LVM followed by excision. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Recently, conservative treatment has become an alternative for managing orbital lymphangioma, which causes no visual deficits or cosmetic issues [8,12]. Based on previous reports, nonsurgical strategies for orbital lymphatic venous malformations are sclerosing therapy, including ethanol, OK-432, sodium tetradecyl sulfate (Sotradecol, Mylan), morrhuate sodium, doxycycline, bleomycin, and pingyangmycin [3,14,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, conservative treatment has become an alternative for managing orbital lymphangioma, which causes no visual deficits or cosmetic issues [8,12]. Based on previous reports, nonsurgical strategies for orbital lymphatic venous malformations are sclerosing therapy, including ethanol, OK-432, sodium tetradecyl sulfate (Sotradecol, Mylan), morrhuate sodium, doxycycline, bleomycin, and pingyangmycin [3,14,28].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous reports, nonsurgical strategies for orbital lymphatic venous malformations are sclerosing therapy, including ethanol, OK-432, sodium tetradecyl sulfate (Sotradecol, Mylan), morrhuate sodium, doxycycline, bleomycin, and pingyangmycin [3,14,28]. Other Lately, the use of oral sildenafil for the treatment of microcystic lesions has been reported [8]. Sildenafil reduces contractility of vascular smooth muscles and causes cystic lesions to collapse [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar case has been reported that an orbital lymphaticovenous malformation was accompanied by an arteriovenous fistula. In that case, coil embolization and sclerotherapy were performed followed by resection [ 5 ]. The patient in the present case had a relatively well-demarcated OVM but without surgical intervention of the intraorbital lesion, it was successfully regressed after intracranial feeder vessel cauterization.…”
mentioning
confidence: 99%